Refleksi Guru dalam Pembelajaran Sosial Emosional Bagi Anak Usia Dini dan Anak Berkebutuhan Khusus di TK Kristen Gamaliel Palu - Patikan, Krisnawati; Windarti, Maria Titik (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
Teacher reflection plays an important role in improving the quality of social-emotional learning for early childhood, including children with special needs. Through continuous reflection, teachers can evaluate and improve learning practices by paying attention to the emotional, social, and developmental aspects of children holistically. At Palu Christian Kindergarten, integrated and experience-based social-emotional learning, such as STOP exercises, collaborative activities, and simple reflection, has been proven to support children's self-awareness, emotion management, empathy, and responsibility. The success of this learning is influenced by a safe, inclusive, accepting environment, as well as support from families and schools. Although it has been running well, learning can still be developed through the use of technology and innovative activities. Thus, consistent teacher reflection and a conducive environment are key to optimizing the social-emotional development of early childhood and children with special needs.